Beyond spreadsmeasuring sovereign market stress in the euro area - Carlos Garcia de Andoain; Manfred Kremer (European Central Bank (ECB), 2018)
In this paper we propose a composite indicator that measures multidimensional sovereign bond market stress in the euro area as a whole and in individual euro area member states. It integrates measures of credit risk, volatility and liquidity at short-term and long-term bond maturities into a broad measure of sovereign market stress. The statistical framework builds on that of the ECB's Composite Indicator of Systemic Stress (CISS) developed by Hollo, Kremer and Lo Duca (2012), so that we call our metric the Composite Indicator of Systemic Sovereign Stress or 'SovCISS'. We implement the SovCISS for eleven euro area member states and also present four options of a SovCISS for the entire monetary union. In addition, we suggest a linear decomposition of the SovCISS, singling out contributions of the different components and of the time-varying correlations across these components. Comparing develoments in the SovCISS and the CISS over the crisis period clearly illustrates the usefulness of the latter for the real-time monitoring of systemic instabilities in the financial system as a whole. Finally, an application of the country-specific SovCISS indicators to the VAR-based spillover literature suggests that stress mainly originates from a few euro area countries, and that spillover patterns vary over time.
Keywords: C43; E44; F45; G01; H63; 330; financial stress index; systemic risk; sovereign debt crisis; spillover index